Determination of the ballistic performance ramie-fiber-reinforced epoxy composite-sic ceramic in multilayered armor system - Mukhammad, Alaya Fadllu Hadi; Rusnaldy; Ismail, Rifky; Riyadi, Tri Widodo Besar (Eastern-European Journal of Enterprise Technologies, 2023)
Multilayered Armor System (MAS) is being extensively studied around the world for its ability to retain ceramic fragmentation after a collision occurs. MAS consist of a ceramic layer placed at the front and supported by a composite layer of ramie-fiber-reinforced epoxy resin. Present study utilizes natural fibers of 50 % ramie fibers with epoxy resin as the matrix and Silicon Carbide (SiC) ceramic as the front panel. The ballistic testing in this study used 7.62×51 mm NATO Ball projectile with a firing distance of 15 m from the bullet panel. The velocity of projectile was detected using LIGHT SCREEN B471 type. The aim of the study is to conclude the optimal thickness of ramie fiber-epoxy and SiC ceramics MAS structure based on experiments which can withstand 7.62 NATO ball bullet penetration. To achieve this aim, the following objectives are accomplished: study the effect of SiC ceramic addition to ramie composite on BFS and study the effect of SiC ceramic addition to ramie composite on failure mode. Results show that the addition of the number of layers of SiC increases resistance of ballistic MAS marked by a decrease in the value of BFS clay. The 5SiC+10R is the optimal thickness in resisting the penetration of 7.62×51 mm bullets with 12 mm BFS clay. Failure phenomena found in this study were projectile fragments, matrix cracks, radial cracks, impact points, and ceramic fragments. Matrix crack formation appears on 5SiC+10R with mini deformation in rear side. Phenomenon of ceramic fragmentation in the shot causes the MAS structure to be damaged, so that the ramie fiber composite layer will face the bullet directly if it is subjected to a second shot. Ultra High Hardness Armor (UHHA) as first layer on the MAS structure is an attractive option for further research.